2006
DOI: 10.1309/ebcb-6h54-k1n2-p9ql
|View full text |Cite
|
Sign up to set email alerts
|

The Binding of Thyroid Transcription Factor-1 and Hepatocyte Paraffin 1 to Mitochondrial Proteins in Hepatocytes

Abstract: We studied the antibodies hepatocyte paraffin 1 (Hep Par 1) and thyroid transcription factor-1 (TTF-1; clone 8G7G3/1) in normal human liver tissue with immunoelectron microscopy using renal tubules as control samples. TTF-1 (8G7G3/1) and Hep Par 1 bound exclusively to the mitochondria of hepatocytes but not to those of the renal tubular epithelium. Both antibodies labeled mitochondria in a similar pattern and density. These findings confirm that the binding site of Hep Par 1 in hepatocytes is mitochondrial. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…75 The different cellular and structural antigenic targets, broad spectrum of clinical situations in which IHC is used, and the lack of consistent, reliable, external and internal control standards, makes this an unrealistic goal. [97][98][99] In the absence of a universal IHC assay scoring system, responsibility rests with the pathologist to provide this information in the report. It is important that pathologists understand the transport pathways of these proteins and restrict interpretation to the relevant subcellular structures as reported in the literature by that specific antibody clone.…”
Section: Commentsmentioning
confidence: 99%
“…75 The different cellular and structural antigenic targets, broad spectrum of clinical situations in which IHC is used, and the lack of consistent, reliable, external and internal control standards, makes this an unrealistic goal. [97][98][99] In the absence of a universal IHC assay scoring system, responsibility rests with the pathologist to provide this information in the report. It is important that pathologists understand the transport pathways of these proteins and restrict interpretation to the relevant subcellular structures as reported in the literature by that specific antibody clone.…”
Section: Commentsmentioning
confidence: 99%
“…20 In that study, Western blot analysis with cellular proteins extracted from normal human liver demonstrated that Hep Par 1 and TTF-1 bound to a protein band of approximately 150 kd. The authors speculated that different epitopes to Hep Par 1 and TTF-1 share the same protein molecules in hepatocyte mitochondria, and we completely agree.…”
Section: Discussionmentioning
confidence: 89%
“…Hepatocyte paraffin-1 (HepPar-1) is a mouse monoclonal antibody that reacts with a poorly characterized antigen present in hepatocytes, probably within mitochondria 63 . However, studies have also shown that HepPar-1 can be expressed in carcinomas from the pancreatobiliary tree, the tubular gastrointestinal tract, lung and genitourinary tract 64 .…”
Section: Discussionmentioning
confidence: 99%